KECERNAAN IN VITRO SERAT KASAR DAN PROTEIN KASAR PAKAN RUMINANSIA BERBASIS Indigofera sp. DENGAN KONDISI BAHAN YANG BERBEDA - Miftah Reza Tama Faturohman; Imbang Haryoko; Nur Hidayat (Fakultas Peternakan Universitas Jenderal Soedirman, 2022)
Background. The research activity has the aim of studying the effect of the addition of Indigofera sp. form of fresh, hay, and flour for best digestibility of crude protein and crude fiber in vitro. Materials and Methods. The material used, are Indigofera sp. in fresh, hay, and flour form, commercial concentrate, H2SO4, goat’s rumen fluid, hot H2O, acetone, NaOH, HCl, PP indicator, and tools such as Erlenmeyer, blender, oven, scales, porcelain dish, funnel, filter paper, desiccator, kjeidahl, flask, and destilator. The method used for in vitro experimental research using Completely Randomized Design (CRD) with 4 treatments repeated 5 times, data analyzed by ANOVA and further tests using Honest Significant Difference (BNJ) test. The forms of treatment given were P0 without adding indigofera, P1 adding fresh indigofera as much as 40%, P2 adding dry indigofera as much as 40%, and P3 adding flour indigofera as much as 40%. Results. Based on the research, the average crude protein digestibility of each P0 was 49.27±1.85%, P1 was 56.67±3.06%, P2 was 52.87±1.28%, and P3 was 60, 18±2.66%, while the digestibility of crude fiber was respectively 78.46±2.82%, P1 was 75.31±1.27%, P2 was 77.48±3.86%, and P3 of 75.21±3.46%.The results of the analysis of variance showed that the administration of Indigofera sp. with different forms gave a very significant effect (P>0.01) on the digestibility of crude protein and had no significant effect (P<0.05) on the digestibility of crude fiber. The results of the further test of Honest Significant Difference (BNJ) showed that the use of 40% Indigofera sp. fresh form was significantly different with the use of 40% Indigofera sp. flour form, the use of Indigofera sp. 40% fresh form was not significantly different when compared with the administration of Indigofera sp. form of hay, and the use of 40% Indigofera sp. hay was significantly different with the administration of 40% Indigofera sp. lour form. Conclusion. Based on the results of the study showed that the use of Indigofera sp. in the form of flour has a good digestibility value when compared to fresh and dry forms.